2015
DOI: 10.3892/ijo.2015.3145
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiles of cancer stem cells in head and neck squamous cell carcinoma

Abstract: Increasing evidence indicates that cancer stem cells have essential roles in tumor initiation, progression, metastasis and resistance to chemo-radiation. Recent research has pointed out biological importance of microRNAs in cancer stem cell dysregulation. Total number of mature microRNAs in human genome increased to more than 2,500 with the recent up-date of the database. However, currently no information is available regarding microRNA expression profiles of cancer stem cells in head and neck squamous cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
0
13
0
2
Order By: Relevance
“…Next, Bcl-w-overexpressing CM additionally contributed to increased sphere-formation ability in the two GBM cell lines (Figure 1G). Sphere-formation assay is known as a method to confirm the stemness maintenance, one of the cancer malignant features 17, 18, 19. Sox2, Oct4, and Notch2,20, 21 together with Musashi-1, Nestin, and CD133, are known as cancer stem-like cell markers in GBM 22, 23.…”
Section: Resultsmentioning
confidence: 99%
“…Next, Bcl-w-overexpressing CM additionally contributed to increased sphere-formation ability in the two GBM cell lines (Figure 1G). Sphere-formation assay is known as a method to confirm the stemness maintenance, one of the cancer malignant features 17, 18, 19. Sox2, Oct4, and Notch2,20, 21 together with Musashi-1, Nestin, and CD133, are known as cancer stem-like cell markers in GBM 22, 23.…”
Section: Resultsmentioning
confidence: 99%
“… 45 In HNC CSCs, miR-424, let-7a, miR-6836, and miR-6873 are lower expressed than miR-147b and miR-7152. 46 Especially, miRNA-34a is shown to repress EMT, aldehyde dehydrogenase activity, invasiveness, and clonogenicity of CSCs in HNSCC. 47 However, potential pathways involved in these processes have not been described in detail, and thus further work will be needed in the future.…”
Section: Dormancy-related Cancer Cellsmentioning
confidence: 99%
“…Likewise, a meta-analysis declared that ALDH1 positive patients had worse prognosis associated with common clinicopathological features and poor prognostic factors (45). Also, Yata et al showed that increased ALDH1 activity HNSCC cells represent CSC (46). We have displayed the expression of ALDH1a expression in tumor spheres of UTSCC-60A cell line while confirming CSC isolation.…”
Section: Discussionmentioning
confidence: 99%